INFLUENCE OF ULŪL ALBĀB ON SUSTAINING COMPETITIVE ADVANTAGE OF SMALL BUSINESSES IN MALAYSIA - Suhaimi Mhd Sarif; Yusof Ismail; Dolhadi Zainudin, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Small businesses in Malaysia encounter difficulties in sustaining their competitive advantage in rapidly evolving markets. To effectively address this problem, owners and strategists of small businesses should possess technical knowledge, intelligence, and strategic insight that is known as ulūl albāb. The objective of this study is to investigate the influence of ulūl albāb on the formulation, implementation, and evaluation of strategies by owners and strategists of small businesses in Malaysia, with the goal of sustaining their competitive advantages in a rapidly changing market environment. This study used qualitative research through personal interviews with five owners and strategists of small businesses. The interviews provided valuable insights into their comprehension and utilisation of ulūl albāb characteristics on the decision-making procedures employed by the strategists. The results suggest that although the strategists recognised the significance of ulūl albāb qualities, most of the situation their decision-making process was impacted by emotions and sentiments. The presence of emotional involvement posed difficulties in the preservation of corporate continuity. This findings provides insights on the influence of ulūl albāb characteristics on strategic thinking that led to practical and helpful suggestions for small business owners and strategists. This implies the necessity of implementing training and development initiatives specifically designed to enhance these qualities within practical business environments, hence facilitating the ability of small enterprises to adjust and prosper in highly competitive marketplaces.